A Cartographic Approach To The Right Periphery: The Dual Status Of Italian Sembrare And Its Korean Counterpart*. (9th April 2022) - An, Duk‐Ho
Abstract: The cartographic project aims at drawing a map of clause structure that is as precise and as detailed as possible (Cinque 1999, 2004, Rizzi 1997, among many others). In this paper, I focus on the distribution of heads in the right periphery in Korean that I argue provides a direct window into the clausal architecture of the language. Taking as a starting point Cinque's (2004) discussion on the Italian verb sembrare in the context of clitic climbing and restructuring (see also Haegeman 2006, 2010), I examine the behavior of the verb pota in Korean and show that the verbs in question behave in exactly the same way in crucial respects—they can be merged high as functional heads marking speaker‐related evidentiality, while they can also be merged low as lexical verbs. The parallelism between pota and sembrare provides strong evidence for the universality of the cartographic hierarchy of functional projections.